The Politics and strategy of nuclear weapons in the Middle East : opacity, theory, and reality, 1960-1991 : an Israeli perspective - Aronson, Shlomo, 1936- (State University of New York Press, 1992)
Annotation Aronson (political science, Hebrew U., Jerusalem) explains Israel's acquisition and political use of nuclear weapons as a central factor in its foreign policy over the last three decades, emphasizing Israeli and Arab perceptions of each other, the changing roles of the US and USSR, and the nuclear element in the Gulf War and the Intifada. Paper edition (unseen), $19.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Middle East -- Military policy.; Israel -- Military policy.; Nuclear weapons -- Middle East.; Nuclear weapons -- Israel.; Nuclear nonproliferation.; Armes nucléaires -- Moyen-Orient.; Armes nucléaires -- Israël.; Non-prolifération nucléaire.; Israël -- Politique militaire.; Moyen-Orient -- Politique militaire.; TECHNOLOGY & ENGINEERING -- Military Science.; HISTORY -- Military -- Other.; Military policy; Nuclear nonproliferation; Nuclear weapons; Israel; Middle East